STUDI PENGARUH GERAK VOEDING TERHADAP KEKUATAN TARIK DAN KETANGGUHAN IMPAK SAMBUNGAN FRICTION STIR WELDING (FSW) PADA ALUMINIUM PADUAN - Fans Onana Momow,; Wartono,; Rivan Muhfidin, (ReTII, 2022)
Friction Stir Welding (FSW) is a welding process utilizing heat due to rotation of the tool rubbing against the base metal under high axial pressure in the welding area. This study aims to determine the effect of variations in voeding motion (feed rate) on the mechanical properties and microstructure of similar metal joints, namely aluminum alloy with a thickness of 3 mm. The FSW process uses a milling machine with a butt joint type of welding connection. The constant rotation speed of the tool is 910 rpm. The tilt angle of the tools is 2Â°. The voeding motion parameter variation (feed rate) is 120 mm/min and 180 mm/min. The research method was carried out on a 6xxx aluminum plate with a size of 300 x 100 x 3 mm. The machine used is Aciera brand CNC milling machine. The design tools are 115 mm long, 20 mm in diameter, and 2.6 mm high pin. The tests carried out are composition testing, micro and macro structure, tensile testing, and impact testing. The results of the composition test show that Al has an aluminum (Al) composition of 98.27%. In addition to aluminum, there is an element of magnesium (Mg) which dominates at 0.412%. And the element silicon (Si) is 0.609%. And the results of the tensile test on the raw material specimen obtained a tensile stress value of 338.9 MPa. After friction stir welding, the two voeding motion variables obtained the highest tensile stress value for the voeding motion variable V2 = 180 mm/minute, which is 200.8 MPa. And the lowest tensile stress value in the voiding motion V1 = 120 mm/minute is 191.8. Then the results of impact testing on raw material specimens obtained a low impact price of 0.32 J/mm2. After friction stir welding of the two voeding motion variables, the highest impact value on the voeding motion variable V2 = 180 mm/minute is 0.39 J/mm2 then the impact value decreases on the voeding motion V1 = 120 mm/minute of 0.35 J/mm2